FOLLOWING THE SUFFERING MESSIAH: AN EXEGESIS OF MARK 8:27–33 AND A CRITIQUE OF THE THEOLOGY OF GLORY IN THE CONTEMPORARY CHURCH: MENGIKUTI MESIAS YANG MENDERITA: EKSEGESIS MARKUS 8: 27-33 DAN KOREKSI ATAS TEOLOGI KEMULIAAN DALAM GEREJA MASA KINI - Ageng Pamarto (RERUM: Journal of Biblical Practice, 2026)
AbstractThis study examines the concept of the suffering Messiah in Mark 8:27–33 as a corrective to the theology of glory prevalent in contemporary churches. The central problem addressed is the tendency of Christian communities to confess Jesus as the Messiah while neglecting or rejecting suffering as an essential dimension of His identity and mission. The purpose of this research is to provide an exegetical interpretation of Mark 8:27–33 and to explore its theological and practical implications for contemporary Christian discipleship. The study employs a grammatical-historical exegetical method, incorporating historical context, narrative structure, textual criticism, and grammatical-lexical analysis of the Greek New Testament text. The findings demonstrate that Mark intentionally presents Peter’s confession and Jesus’ prediction of suffering as a theological turning point in the Gospel, correcting messianic expectations shaped by triumphalism. The suffering of the Messiah is portrayed as a divine necessity (???) within God’s redemptive plan rather than a failure of mission. Consequently, following Christ entails taking one’s place behind Him on the path of the cross. This study concludes that Mark 8:27–33 offers a significant theological critique of the theology of glory and reaffirms a model of discipleship grounded in the cross, obedience, and faithfulness amid suffering.   AbstrakPenelitian ini membahas pemahaman tentang Mesias yang menderita dalam Markus 8:27–33 sebagai koreksi terhadap teologi kemuliaan yang berkembang dalam gereja masa kini. Masalah utama yang dikaji adalah kecenderungan gereja dan jemaat untuk mengakui Yesus sebagai Mesias, tetapi menolak atau mengabaikan dimensi penderitaan sebagai bagian integral dari identitas dan misi-Nya. Tujuan penelitian ini adalah untuk menafsirkan secara eksegetis perikop Markus 8:27–33 serta menyingkapkan implikasi teologis dan praktisnya bagi pemuridan Kristen kontemporer. Metode yang digunakan adalah eksegesis gramatikal-historis dengan menganalisis konteks historis, struktur naratif, data tekstual, serta aspek gramatikal dan leksikal teks Yunani Perjanjian Baru. Hasil penelitian menunjukkan bahwa Markus secara sengaja menempatkan pengakuan Petrus dan nubuat penderitaan Yesus sebagai titik balik teologis Injil, guna meluruskan ekspektasi mesianik yang berorientasi pada kemuliaan. Penderitaan Mesias dinyatakan sebagai keharusan ilahi (???) dalam rencana Allah, bukan sebagai kegagalan misi. Dengan demikian, mengikuti Kristus berarti bersedia berjalan di belakang-Nya dalam jalan salib. Penelitian ini menyimpulkan bahwa Markus 8:27–33 memberikan koreksi teologis yang signifikan terhadap teologi kemuliaan dan menegaskan kembali pemuridan yang berakar pada salib, ketaatan, dan kesetiaan di tengah penderitaan.